2009
DOI: 10.1001/archophthalmol.2008.602
|View full text |Cite
|
Sign up to set email alerts
|

Early Effects of Intravitreal Triamcinolone Acetonide on Inflammation and Proliferation in Human Choroidal Neovascularization

Abstract: To evaluate the early effects of triamcinolone acetonide (TA) on inflammation, proliferation, and vascular endothelial growth factor (VEGF) in human choroidal neovascularization (CNV). Methods: Retrospective review of an interventional case series of 29 patients who underwent macular translocation. Fourteen CNV membranes without previous therapy (control CNV group) and 4 CNV membranes excised 3 days after photodynamic therapy (PDT CNV group) comprised the control groups. Eleven patients were treated with intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 58 publications
(117 reference statements)
0
10
0
Order By: Relevance
“…Most CNV occurs in macular lesions at the center of the retina and directly causes a severe loss of visual acuity [1,2,3,4]. Inflammation-induced VEGF-A production is essential for development of CNV [5,6,7,8,9,10,11,12]. However, although anti-VEGF-A treatments have proven therapeutic effects, the outcome remains unsatisfactory.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most CNV occurs in macular lesions at the center of the retina and directly causes a severe loss of visual acuity [1,2,3,4]. Inflammation-induced VEGF-A production is essential for development of CNV [5,6,7,8,9,10,11,12]. However, although anti-VEGF-A treatments have proven therapeutic effects, the outcome remains unsatisfactory.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory processes are thought to be critical in generating CNV [5,6,7]. Many experimental and clinical studies have indicated that the vascular endothelial growth factor A (VEGF-A) family, especially VEGF-A, is essential for promoting CNV [8,9,10,11,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intravitreal application of triamcinolone acetonide as adjuvant to PDT or monotherapy does not suppress VEGF but enhances endostatin expression in CNV. Therefore, in CNV treated with triamcinolone acetonide monotherapy or PDT–triamcinolone acetonide combination therapy, the VEGF predominance score over endostatin is reduced to its level in control CNV 47. However, bevacizumab seems to have a dual effect in angiogenesis inhibition by reducing intensity of VEGF expression besides enhancing endostatin.…”
Section: Discussionmentioning
confidence: 99%
“…However, in vivo studies demonstrated that TA strongly inhibits VEGF and stromal-derived factor-1 levels inside the vitreous as well [126]. Other recent studies on immunohystochemical staining reported that TA seems to exert its angiogenesis inhibitory effects on CNV by enhancing endostatin expression rather than by suppressing VEGF expression [127].…”
Section: Mechanism Of Action Of Triamcinolone Acetonidementioning
confidence: 97%